Hubungan Efikasi diri Masyarakat terhadap Vaksinasi COVID-19 di Puskesmas Siak Hulu I Kabupaten Kampar Tahun 2021 : Community Self-Efficacy Relationship to COVID-19 Vaccination at Puskesmas Siak Hulu I Kampar Regency in 2021 - Nopriadi Nopriadi; Musfardi Rustam; Aminatul Fitri (Jurnal Kesehatan Komunitas, 2022)
The high massive transmission of COVID-19 occurs great numerous of mortality and morbidity. It is caused by low coverage of COVID-19 vaccinations that are continuously pursued by the Indonesian government. This can be identified by health promotion based on community self-efficacy as effective prevention of COVID-19 has not been fully implemented. Public understanding and perception of the prevention of COVID-19 are highly expected. Public confidence or known self-efficacy is needed in supporting COVID-19 vaccination.  This study aims to find out the relationship of community self-efficacy to COVID-19 vaccination at the Siak Hulu I Health Center in Kampar Regency in 2021. This was an analytic quantitative study with a cross-sectional approach to 209 participants which was taken by simple random sampling technique in Puskesmas Siak Hulu I. Based on the chi-square test result, it was found a relationship between self-efficacy and COVID-19 vaccination. The results showed that a person has a high self-efficacy greater than 5 times more vaccination than someone who has low self-efficacy. It is recommended to increase self-efficacy through good and easy-to-understand health communication about COVID-19 vaccination in the community.